(untitled) (REMUNOM, 2024)
Incluir o resumo em inglês. The paper aims to analyze the use of marketing in the public sector, focusing on how strategies from this discipline can improve the relationship between government and citizens. The main objective is to identify how marketing can increase efficiency, transparency, and public participation. The research also addresses the challenges and improvements in implementing marketing campaigns in the public service. The study adopted an integrative bibliographic methodology, reviewing theses, dissertations, and other academic works on marketing in the public sector. Concepts, reflections, and criticisms were analyzed to provide a robust theoretical basis. The main theorists underpinning the work include Cezar (2019), Brito (2023), and Carvalho (2023). These authors offer significant contributions to services marketing, social marketing, and the peculiarities of applying these theories in the public sector. The results indicate that marketing can be a powerful tool for the public sector by improving communication, increasing transparency, and strengthening citizens’ trust in institutions. However, challenges such as resistance to change and lack of resources limit its practical application. The research concludes that, with strategic planning and a focus on the citizens, it is possible to modernize public management, making it more efficient and closer to the population’s needs.